The Second-Person Perspective - Pauen, Michael (Inquiry (Oslo), 2012)
The rise of social neuroscience has brought the second-person perspective back into the focus of philosophy. Although this is not a new topic, it is certainly less well understood than the first-person and third-person perspectives, and it is even unclear whether it can be reduced to one of these perspectives. The present paper argues that no such reduction is possible because the second-person perspective provides a unique kind of access to certain facts, namely other persons' mental states, particularly, but not only, in social contexts. The paper starts with the idea that perspectives are ways of epistemic access that determine an epistemic subject's recognition of a certain object. While the first-person perspective is subjective because it is based on, and directed at, the epistemic subject's experiences, the third-person perspective, which is based on objective evidence and gives access to all kinds of entities, is objective. The second-person perspective, by contrast, is intersubjective because it is a relation between an epistemic subject and another sentient being's mental states. It involves the epistemic subject's replication of those states, a basic self/other distinction and a basic awareness of the relevant situational differences between the epistemic subject and the other being. This is why the second-person perspective is a perspective on a perspective, which involves a basic awareness of perspectivalness, even if second-person perspective taking may be subpersonal to a large extent.